LEGAL CHARACTERISTICS OF THE SUBJECT STRUCTURE OF LEGAL RELATIONS ARISING IN CONNECTION WITH THE CIRCULATION OF VIRTUAL ASSETS - Ushynkina, Oleksandra (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: study of modern trends and criteria for determining the subject structure of legal relations arising in connection with the circulation of virtual assets, and borrowing the most relevant approaches into Ukrainian legislation. Research methods: in the course of the work, general scientific and special scientific methods of cognition were used, including: methods of analysis and synthesis, which were used to research the legislation of different countries; the comparative legal method, which is used when comparing homogeneous legal norms; a historical-legal method, which is used to study the retrospective development of approaches to determining the range of subjects of legal relations arising in connection with the circulation of virtual assets in regulatory acts. Results: modern global approaches to determining the range of subjects of legal relations arising in connection with the circulation of virtual assets are outlined; the main trends in the context of determining the subject composition of legal relations arising in connection with the circulation of virtual assets are defined and formulated. Discussion: the study of foreign and domestic approaches to determining the subject composition of legal relations arising in connection with the circulation of virtual assets and their classification is of significant importance for the development of Ukrainian legislation, which only partially corresponds to current trends. Such trends are the application of a broad approach to determining the subject structure of legal relations arising in connection with the circulation of virtual assets; regulation of the legal status of each of the subjects, as well as the entire scope of rights and obligations. Ukrainian legislation in the field of regulation of virtual assets in terms of defining the range of subjects of legal relations arising in connection with the circulation of virtual assets does not fully correspond to current approaches, since the legislator does not take into account a number of important aspects that relate specifically to the list of these subjects.